Monitoring of Water Quality the Need of Present Day House Hold Water Management (Indian Journal of Public Health Research & Development, 2021)
WHO 2019 report on drinking water says that In 2017, 71% of the global population (5.3 billion people)used a safely managed drinking-water service – that is, one located on premises, available when needed, andfree from contamination.. Most countries, the proportions of piped and other-improved water supplies arefaecally contaminated sources due to lack of basic sanitary protection against contamination. Contaminatedwater is an important contributor to water borne disease including hepatitis A,cholera, typhoid, andpoliomyelitis.1 For people with enough water supply can treat their water at home after testing water qualityto ensure microbiological quality. Treating water at the household level or other point of use also reduces therisk of waterborne disease arising from recontamination during collection, transport, and use in the home.This article mainly focuses on need for water quality monitoring,water quality, types of water quality testingthe importance of water quality monitoring and reviews related to water quality testing.
Keywords: Water quality, drinking water, tests in monitoring water quality, water quality standards.